Device-measured physical activity and sedentary time in the Nordic countries: A scoping review of population-based studies - Ing-Mari Dohrn; Jakob Tarp; Jostein Steene-Johannessen; Tommi Vasankari; Maria Hagströmer (Elsevier, 2024)
Purpose: The purpose of this scoping review was to summarize and describe the methodology and results from population-based studies of physical activity and sedentary time measured with devices in the Nordic countries (Denmark, Finland, Iceland, Norway, and Sweden) and published in 2000 or later. Methods: A systematic search was carried out in PubMed and Web of Science in June 2023 using predefined search terms. Results: Fourteen unique research projects or surveillance studies were identified. Additionally, 2 surveillance studies published by national agencies were included, resulting in a total of 16 studies for inclusion. National surveillance systems exist in Finland and Norway, with regular survey waves in school-aged children/adolescents and adults. In Denmark, recent nationally representative data have been collected in school children only. So far, Sweden has no regular national surveillance system using device-based data collection. No studies were found from Iceland. The first study was conducted in 2001 and the most recent in 2022, with most data collected from 2016 to date. Five studies included children/adolescents 6-18 years, no study included preschoolers. In total 11 studies included adults, of which 8 also covered older adults. No study focused specifically on older adults. The analytical sample size ranged from 205 to 27,890. Detailed methodology is presented, such as information on sampling strategy, device type and placement, wear protocols, and physical activity classification schemes. Levels of physical activity and sedentary time in children/adolescents, adults, and older adults across the Nordic countries are presented. Conclusion: A growing implementation of device-based population surveillance of physical activity and sedentary behavior in the Nordic countries has been identified. The variety of devices, placement, and data procedures both within and between the Nordic countries highlights the challenges when it comes to comparing study outcomes as well as the need for more standardized data collection.